TUG1, SPRY4-IT1, and HULC as valuable prognostic biomarkers of survival in cancer: A PRISMA-compliant meta-analysis. Issue 46 (November 2017) - Zhong, Yucheng; Chen, Zhicong; Guo, Shuyuan; Liao, Xinhui; Xie, Haibiao; Zheng, Yien; Cai, Bin; Huang, Peixian; Liu, Yuhan; Zhou, Qun; Liu, Yuchen; Huang, Weiren
Abstract: Background: Long noncoding RNAs (LncRNAs) are involved in the development and progression of various cancers. Accumulating evidences indicated that expression of lncRNAs was related to the prognosis of tumors. Methods: Here, 3 well-known lncRNAs associated with cancer were gathered to prove the potential role of lncRNAs as novel predictors of survival in human cancer. This meta-analysis collected all eligible studies about TUG1, SPRY4-IT1, and HULC and explored the relationship between lncRNAs expression and lymph node metastasis (LNM) or overall survival (OS). A comprehensive, computerized literature search was undertaken by using PubMed, EMBASE, Cochrane Library, and Web of Science (up to October 10, 2017). Strength of association between 3 lncRNAs and cancer prognosis was assessed by computing the hazard ratios (HR) with its corresponding 95% confidence interval (CI). According to the inclusion and exclusion criteria, respectively, 10, 9, and 7 studies of 3 lncRNAs were included in this meta-analysis. Results: In the current meta-analysis, it could be concluded that the expression of these 3 lncRNAs in tumor tissues is not a direct evidence of LNM. In general, there was a significant negative correlation between TUG1 levels and OS time (pooled HR 1.54, 95% CI 1.06–2.24), SPRY4-IT1 levels and OS time (pooled HR 2.12, 95% CI 1.58–2.86) and HULC levels and OS time (pooled HR 2.10, 95% CI 1.18–3.73). It could be revealed from the result that high level expression of these 3 lncRNAs might be correlated with a bad prognosis. Conclusions: In conclusion, the current meta-analysis demonstrated that TUG1, SPRY4-IT1, and HULC might serve as a moderate predictor of survival in human cancer. Abstract : Supplemental Digital Content is available in the text